Knowledge, attitude and practices of vegetable farmers on pesticide safety in Songco, Lantapan, Bukidnon - Guinitaran, Karl Jay Guray
Agriculture is the bakcbone of the Philippine economy and farming is still the most common form of employment. The expanded access to pesticides during the 1960s, through the Masagan Project, led to inadvertent use of pesticides by the Filipino farmer (Ohayo-Mitoko, 1997). Since farming system promotes the reliance on agrochemicals, environmental health effects were observed in various literatures such as the study of Dano (2001) which showed traces of pesticides in various river systems in Latapan, Bukidnon, Wilson and Tisdel (2001) and Dioquino (2002) who reported cases of pesticide poisoning in the Philippines from various routes of exposures. Rola and Pinali (1993) reported gaps in the preparation and application of pesticides. Due to the identified gaps in safety practices in the use of pesticides, a cross-sectional analytic method of research was designed to determine the association between knowledge, attitude and practices of vegetable farmers in Songco, Lantapan in the province of Bukidnon, Philippines from February to July of 2014. The researcher interviewed 139 vegetable farmers using a pre-tested interview schedule. Field and safety practices on pesticide use was then summarized and tested for association with KPA parameters. Correlates of ?good knowledge? level was identified using Logistic Regression analysis. The study found that farmers have unrestricted access to pesticides within the area. There were farmers who do not use the appropriate personal protective equipment during preparation and application of pesticides, likewise, some farmers rinse their sprayers in the Alanib river which could harm the biodiversity in its aquatic ecosystem notwithstanding the residents who source their water supply from the river. Most of the farmers store the chemicals at home and there are a few who store them near their kitchen. There were three reported cases of accidental poisoning through consumption of food item, and ingestion of inappropriately labelled container. With regard to the knowledge level of the farmers, majority had good pesticide safety knowledge level. Among attitude parameters, majority believed that pesticides are required to increase crop yield and that all types of insects are harmful to the crops. Regarding compliance to safety practices when handling pesticides, most farmers do not own or use goggles. Few of the farmers in this study eat, drink, and smoke cigarette when handling pesticides. Take-home exposure pathway can be attributed to some farmers who reportedly do not wash their hands and change clothes after handling pesticides and mix their pesticide-contaminated clothes with the household laundry. There had been significant association between knowledge level and the farmer's practice of changing clothes after application of pesticides (p=0.021) and the farmer's attitude of seeking assistance to the municipal agriculture's office and attendance to the trainings of the municipal agriculturists' office (p=0.039). The identified correlates of good knowledge level on pesticide safety are sex ( female, OR=3.42) and educational attainment (_< elementary graduates, OR=6.14)....